The teratogenic effect of pregabalin on heart, liver and kidney in rats: a light microscopic, electron microscopic and immunohistochemical study - Omnia I. Ismail; Eman S. Shaltout; Nora Z. Abdellah; Diab F. Hetta; Wael M. A. Abd El-Ghani; Lobna A. Abdelzaher; Ahmed Mohamed Mohamed Mahmoud; Asmaa M. Hasan; Noha A. Rashed; Noha Esmael Ebrahem (BMC, 2022)
Abstract Background Pregabalin (PGB) was approved as new anti-epileptic drugs with little information about its teratogenic effect. Aim of the work to evaluate the developmental toxicity of PGB. Materials and methods 60 pregnant albino rats were divided into three groups. PGB (500 mg/kg body weight/day) was given to group II, PGB (1250 mg/kg body weight/day) was given to Group III and no medications were given to group I. The pups were normally delivered. Liver, kidney and heart specimens were prepared for histological, immunohistochemical, and morphometric studies. Results A dose of 500 mg of PGB had minimal toxic effects in the form of mild collagen deposition and moderate positive caspase-3 immunoexpression. PGB dose of 1250 mg/kg induced gross toxic effects in form of degenerated cardiac myofibres, ruptured blood vessels, vacuolations in the renal cortex, fibrosis and strong positive caspase-3 immunoexpression. Conclusion PGB at dose of 500 mg/kg revealed minimal toxic changes. PGB cause embryotoxicity in a dose-dependent manner, as the higher dose induced more degenerative changes.